Taxonomy and distribution of diatoms on the Turkish Mediterranean Coast, Dalyan (Muğla) - KALELI, MUHAMMET AYDIN; KOCIOLEK, JOHN PATRICK; SOLAK, CÜNEYT NADIR (Mediterranean Marine Science, 2020)
Diatoms are one of the components in the littoral zone and the most productive in terms of O2 production and primary production. Despite their importance in these coastal ecosystems, the diatoms of littoral zones of Turkish coastlines have been understudied. In this report, we document the littoral diatoms from Dalyan Iztuzu Beach at the southeast coasts of Aegean Sea. Samples were collected from 6 stations in Dalyan Beach between 2012 and 2016. We report here on the occurrence of 9 genera including, Catenula Mereschkowsky, Cymatosira Grunow, Dimeregramma Ralfs, Diplomenora Blazé, Eunotogramma Weisse, Meloneis Louvrou, Danielidis & Economou-Amilli, Neohuttonia Kuntze, Plagiogramma Greville and Tetramphora Mereschkowsky, as well as 40 taxa as newly-recorded from Turkey. The newly-recorded diatoms are characterized in terms of their morphology and illustrated with light micrographs. For each species, their habitat and geographic distribution along the coasts are discussed.